The Internalization of Religious Character Values through Village Local Wisdom at MA Kartika Cendekia Air Lalangi - Ikhsan Tri Hartanto; Syahrul Ramadhan; Rensi Fitriani; Abdul Aziz bin Mustamin; Aam Amaliyah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Digital transformation presents a unique set of challenges and opportunities for Islamic Education (PAI) in rural settings. This study aims to analyze the dynamics of digital literacy implementation at MA Kartika Cendekia, Air Lalangi Village, Ulok Kupai District. Using a descriptive qualitative method, data were gathered through observations, in-depth interviews with teachers and students, and documentation studies. The results reveal that while significant digital infrastructure disparities and accessibility constraints persist, the integration of accessible digital media such as WhatsApp, YouTube, and digital Al-Qur'an applications has successfully transformed traditional religious instruction into a more interactive and visual experience. Furthermore, the study finds that fostering critical literacy through the Islamic principle of Tabayyun and internalizing digital ethics (Akhlak Digital) are essential for students to navigate online religious information safely. The research concludes that despite environmental limitations, rural madrasahs can enhance religious literacy by synergizing technological proficiency with strong moral foundations, ensuring students remain competitive and moderate in the global digital era.